Epidemiological characteristics and importance of lobulation of giant epidermal cysts: An 18-year retrospective review of 19 cases. Issue 31 (5th August 2022) - Lee, Kyu-Il; Namgoong, Sik; You, Hi-Jin; Jeon, Tae-Sung
Abstract : Giant epidermal cysts, which have a diameter of ≥5 cm, have rarely been reported. Giant epidermal cysts that have multiple lobules are referred to as multilocular giant epidermal cysts. This study aims to establish the epidemiological characteristics and statistically determine the significance of lobulation in giant epidermal cysts. Data on 19 patients who developed giant epidermal cysts between January 2003 and February 2021 were retrospectively reviewed. Patients were divided into 2 groups based on the presence of septa and the differences in characteristics were analyzed. Among the 19 patients, 16 (84.2%) were male, and the mean age was 57.7 ± 10.6 years. The mean patient-reported tumor duration was 14.8 ± 12.5 years. Seven (36.8%) patients had multilocular giant epidermal cysts, whereas 12 (63.2%) had unilocular giant epidermal cysts. Compared with unilocular giant epidermal cysts, multilocular giant epidermal cysts had a significantly larger mean diameter (6.0 ± 0.7 vs 8.2 ± 1.8 cm, P = .02) and estimated volume (91.8 ± 43.3 vs 250.0 ± 157.0 mL, P = .02). Giant epidermal cysts have distinctive epidemiologic characteristics with predominance among males, those in their 50s, and a long tumor duration. Multilocular giant epidermal cysts are significantly larger in diameter and volume than unilocular ones.